Influência do laser de alta potência na inibição de processos desmineralizadores do esmalte dental - Tavares, Julieta Gomes (2007)
Artigo 1 - Aim: The aim of this in vitro study was to investigate the effect of Nd:YAG and argon laser irradiations on the enamel acid demineralization by two different chemical laboratory models (pH cycling).Summary background data: The use of lasers to prevent enamel caries has been shown good results, but there are few comparative studies about the effect of different lasers in different pH models cycling.Methods and materials: Twenty one extracted human third molars were sectioned into tooth quarters. The quarters were distributed in three groups: GROUP I (control), non-treated; GROUP II received the Nd:YAG laser irradiation with the following protocol: 60 mJ, 15 pps, 0.9 W e 47.77 J/cm2, 30 seconds; and GROUP III received the argon laser irradiation with the following protocol: 250 mW, 12 J/cm2, 48 seconds. The surfaces were covered with an acid resistent varnish to be immersed in standard acidfied buffer solutions. The tooth quarters were submitted to a two different pH cycling: cycle 1: a 14-day remineralization (6 hours) and demineralization (18 hours) solutions, 37ºC; cycle 2 with 48 hours in demineralization solution. The samples were prepared in slices (60 to 100 μm) to be evaluated by polarized light microscopy. The demineralizations areas were measured (mm2) (n=11). Results: Means followed by different letters are significantly different to ANOVA and Tukey s test (p<0,05): 0.2509 A (control cycle 2); 0.1836 AB (control cycle 1); 0.1782 AB (Nd:YAG cycle 1); 0.1391 BC (argon cycle 2); 0.0927 BC (Nd:YAG cycle 2) e 0.0682 C (argon cycle 1). Conclusion:The results suggest that the treatment with argon laser was more effective, showing the smaller demineralization area by two different pH model cycling. Artigo 2 - Aim: The aim of this in vitro study was to investigate the effect of Nd:YAG and argon laser irradiations on the enamel acid demineralization by a chemical laboratory model to simulate acid erosion lesions.Summary background data: Erosive lesions in enamel are frequently found in patients with gastric-alimentary disturbs. There are no studies examining the use of lasers to prevent enamel erosions.Methods and materials: Third extracted human third molars were sectioned into tooth quarters. The quarters were distributed in three groups: GROUP I (control), non-treated; GROUP II received the Nd:YAG laser irradiation with the following protocol: 60 mJ, 15 pps, 0.9 W e 47.77 J/cm2, 30 seconds; and GROUP III received the argon laser irradiation with the following protocol: 250 mW, 12 J/cm2, 48 seconds. The surfaces were covered with an acid resistent varnish to be immersed in standard acidfied buffer solutions. The tooth quarters were submitted to a pH cycling: 14-day remineralization (6 hours) and demineralization (pH 2,5 - 18 hours) solutions, 37ºC. The samples were prepared in slices (60 to 100 μm) to be evaluated by polarized light microscopy. The demineralizations depths were mesured in mm (n=21). Results: Means followed by different letters are significantly different to ANOVA and Tukey s test (p<0,05): 0.1881 A (control occlusal); 0.1867 A (control cervical); 0.1610 B (argon occlusal); 0.1576 B (argon cervical); 0.1529 B (Nd:YAG occlusal); 0.1481 B (Nd:YAG cervical). Conclusions: The results suggest that the treatment with lasers increased the enamel acid demineralization resistance, so it can be indicated to prevent gastric-alimentary disturbs.